ANALISIS SISTEM PENGGAJIAN DALAM RANGKA MENGEFEKTIFKAN PENGENDALIAN INTERNAL PADA PT. FREIGHT EXPRESS PALEMBANG - Rika Septianis; Dra. Msy. Mikial; Lukita Tripermata (Universitas Indo Global Mandiri)
Payroll data processing system employees at PT.Freight Express Palembang is still simple. Employee data every month is still recorded in a special book, and to submit proof of salary report is still conventional. The problem that arises is the inconsistency of data that can cause data kerangkapan, if the search data takes a very long time because it still uses a conventional system, and data security was still not guaranteed which was implemented well in order to facilitate the processing of payroll, report and salary slip. In this study, qualitative analysis method was used. The data was analyzed by using information and description in the form of prose or standard languages, then it was correlated to other data in order to get clarity of the truth or vice versa, and to obtain new description or to strengthen the description that already existed and vice versa.The type of data used was primary. In collecting the data, interview and documentation were used. The result of the study was expected to be able to provide information about the payroll system so that PT.Freight Express Palembang could control the payroll well and run as expected.Keywords: Internal Control System, Payroll,authorization system